Heterogeneous layer-structured multiphase composite piezoelectret: Fabrication, piezoelectric performance, and application in electromechanical transduction - Shiyu Wu; Xunlin Qiu; Tiantian Gao; Zheng Hu; Yanxun Xiang (AIP Advances)
Piezoelectrets exhibit large piezoelectric sensitivity and high mechanical flexibility, widely employed in sensors, actuators, energy harvesters, etc. In this paper, a heterogeneous-structured multiphase composite piezoelectret (MPCP) was prepared using fluorinated ethylene propylene copolymer (Teflon FEP, 50 μm in thickness), polydimethylsiloxane (PDMS), and polypropylene (PP, 5.8 μm in thickness) films via corona charging, high-temperature curing, and layer stacking techniques. It is shown that the piezoelectric d33 coefficient of the MPCP film reaches a maximum value of about 80 pC N−1 when the surface potential of the FEP film is about 1000 V and the thickness of the PDMS layer is about 80 μm. The d33 coefficient remains stable during two months of storage under laboratory conditions. In addition, the d33 coefficient remains unchanged over 22 000 cycles with a sinusoidal driving force at a frequency of 2 Hz and an amplitude of 1 N. It is found that the d33 coefficient of the MPCP film is strongly dependent on the applied static pressure and the frequency of the dynamic pressure. In addition, the absence of macroscopic air-filled cavities in the MPCP film renders it excellent stability with respect to varying environmental pressure, largely broadening its application scenarios. Due to its large piezoelectric sensitivity and excellent environmental stability, the MPCP sensing film developed here shows promising potential for applications in fields such as flexible sensors, health monitoring, human–computer interfaces, etc.